Virtual training: Three tips, three cons and three pros of online fitness training: Preparing for the "new normal." - Kashubara, K. (Track Coach, 2020)
The pandemic has shut down schools, gyms, tracks, and even parks. This environment makes it difficult for athletes to properly train and for coaches to teach. No one knows when the crisis our world is facing will end. What we should know is that the future is now; and that it is time to prepare for a new normal. Part of that normal will be less physical interaction and more virtual. The transition will be difficult. Yet, the transition must be made none-theless. A coach that follows these guidelines, and has patience, will be stronger, and better prepared for the future.